Electrochemical Behaviour of Graphene Oxide, Reduced Graphene Oxide and Zinc Oxide Graphene Oxide Composite Material Towards Fabrication of Dye Sensitized Solar Cell - Murali, Sandhya; Rajendran, A. Jeya (Asian Journal of Chemistry, 2020)
Graphene oxide (GO), reduced graphene oxide (rGO) and zinc oxide incorporated graphene oxide (ZnO-GO) nanoparticles were synthesized by wet-chemical technique. The ZnO-GO nanocomposite was synthesized from prepared graphene oxide. UV-visible and FTIR spectroscopy confirmed the presence of oxygen functionalities on graphene oxide which was reduced to rGO on treatment with the reducing agent. The XRD patterns revealed the formation of graphene oxide with a characteristic peak at 10.6º which shifted to 24º during the formation of rGO. The crystallite size of all the synthesized material was calculated using Scherrer′s formula. The morphological behaviour of all materials was analyzed by scanning electron microscope (SEM). The electrochemical impedance data and Tafel plots suggested that the composite material has low charge transfer resistance (Rct) and hence could act as a conducting material. The photoelectric conversion values, η for GO, rGO and ZnO-GO were calculated as 2.5, 5.7 and 7.5%, respectively and these values signify that the zinc oxide incorporated graphene oxide material has unique properties of electron transport.